Implementation of the Clearance Settlement System for International Arrival and Departures of Immigration Juanda Surabaya - Wilonotomo Wilonotomo; Firman Wahyu Fachreza (Badan Strategi Kebijakan Hukum, 2022)
The Juanda Surabaya Immigration Manifest System application is an innovation implemented at the Class I Immigration Office for Surabaya Immigration Checkpoint. The implementation of this policy is intended as a basis for making decisions and evaluating the performance that has been carried out. The manifest system is a clearance process to obtain permits for international departures and arrivals. The clearance process is very vital, especially in the supervisory function on aspects of immigration inspection as the enforcement of state sovereignty. It is considered vital because Indonesian citizens and foreign nationals who will enter or leave Indonesian territory will be filtered through the clearance process .This research was conducted by implementing George C. Edward III theory which puts forward4 (four) variables. These variables include communication, resources, attitudes or tendencies (disposition), and bureaucratic structure. A mixed-method of qualitative and quantitative analysis was used for this study. The results obtained are 3.40; 2.04; 3.83 and 3.43;. They show that the manifest system as the completion of the clearance process is a system that can be used as a reference to be implemented at Immigration Checkpoint (TPI), especially at international airports throughout Indonesia.